Interação genótipo x ambiente na reação de progênies de melancia à alternariose no Submédio São Francisco - Lima Neto, Izaias da Silva (Universidade Federal Rural do Semi-Árido, 2009)
This work had the objective to evaluate watermelon genotypes resistance to alternaria leaf blight (Alternaria cucumerina) in two environments (years) in order to identify contrasting and consistent parents as well as to get information related to environmental and genetic effects to support strategies to be followed in watermelon breeding programs. Two experiments were carried out in the Experimental Field of the Department of Technology and Social Sciences (DTCS) at the Campus III of the University of the State of Bahia (UNEB), Juazeiro-BA in the years of 2006 and 2007. In both experiments, the treatments consisted of 14 watermelon genotypes comprising 12 progenies and two checks (Sugar Baby and Charleston Gray cultivars). The seedlings were produced in a green house and were transplanted to the field with previous records of high incidence and severity of the disease. The experimental design was in randomized blocks, with three replications. The plot had five plants spaced 3.0 m between lines and 0.8 m between plants. The irrigation was supplied in furrows. The cultural practices were those normally used for watermelon, but without fungicides. The plants were evaluated 75 days after transplanting using a grading records ranging from: one plants more resistant; to five plants more susceptible. It was found G x A interaction in the evaluation of watermelon genotypes for alternaria leaf blight in the Submiddle São Francisco River Basin with predominance of the complex part of the interaction and that the major part of the phenotypic variance was accounted for genetic factors (74.5%). It was identified a consistent source for resistance to alternaria leaf light represented by the progeny P5 (91-0043) and as a contrasting susceptible parent the Sugar Baby variety was selected. Both, demonstrate a high potential for breeding purposes, and can be used in studies of inheritance of resistance of alternaria leaf blight
Genotype-environment interaction in the reaction of watermelon progenies to alternaria leaf blight in the Submiddle São Francisco region
Keywords: Citrullus lanatus; watermelon breeding; Alternaria cucumerina; Citrullus lanatus; melhoramento de melancia; Alternaria cucumerina; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA